DYNAMICS OF CHANGES IN THE STATE OF HARD DENTAL TISSUES UNDER THE INFLUENCE OF A TREATMENT AND PREVENTION COMPLEX IN CHILDREN WITH MUSCULOSKELETAL SYSTEM PATHOLOGY - Sukhomeylo, D.O.; Reyzvikh, O.E.; Shnaider, S.A.; Sukhomeilo, K.O.; Klenovska, S.V.; Rachynskyi, S.V.; Chertov, S.O. (World of Medicine and Biology, 2024)
The study was dedicated to the evaluation of the impact of the developed treatment and prevention complex on the state of hard tissues of teeth and periodontium in children with musculoskeletal pathology. The study involved 41 children aged 12–15 years with musculoskeletal diseases of various genesis. The studies indicate a fairly high efficiency of the proposed treatment and prevention therapy for children with the above pathology, which included a universal natural biological complex of drugs with a broad therapeutic and preventive effect. The developed treatment and prevention complex helped to stabilise the prevalence of both caries and periodontal diseases. Positive dynamics of clinical indicators of the state of hard tissues of teeth and periodontium was observed against the background of increased serum 25(OH)D levels. Thus, the stable positive therapeutic effect of dental pathology in children with MSS diseases proves the inclusion of medical correction of vitamin D status in the complex treatment. The data obtained are the basis for the implementation of a treatment and prevention complex aimed at helping children with dental and periodontal diseases against the background of musculoskeletal pathology.